2022
DOI: 10.3389/fgeed.2022.974798
|View full text |Cite
|
Sign up to set email alerts
|

The promise of gene editing: so close and yet so perilously far

Abstract: and indels are produced only by the action of the nuclease, have been deregulated in many countries. An exception are those countries within the European Union, where, despite being the third largest producer of genetically engineered crops behind China and the USA, SDN1 crops remain subject to the stringent regulations for genetically modified organisms (GMOs). Such stringent regulations are considered to have a dampening effect on agriculture innovation in the EU, and are perhaps similar to the dampening eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…56 The tendency to patent a new technology and protect it in terms of intellectual property and the benefits arising from this patenting can delay access to a new technology for all people living in a less developed country, regardless of their age, thus ensuring different access and unequal distribution of the benefit of the emergence of these technologies. 57 Baylis et al showed that "A just and equitable society is one with less disparities and more justice. A predictable consequence of allowing (not, encouraging) individuals to genetically modify their children will be greater disparity and greater injustice-and not just because of limited access to genome-editing technology.…”
Section: Individual Autonomymentioning
confidence: 99%
See 1 more Smart Citation
“…56 The tendency to patent a new technology and protect it in terms of intellectual property and the benefits arising from this patenting can delay access to a new technology for all people living in a less developed country, regardless of their age, thus ensuring different access and unequal distribution of the benefit of the emergence of these technologies. 57 Baylis et al showed that "A just and equitable society is one with less disparities and more justice. A predictable consequence of allowing (not, encouraging) individuals to genetically modify their children will be greater disparity and greater injustice-and not just because of limited access to genome-editing technology.…”
Section: Individual Autonomymentioning
confidence: 99%
“…56 The tendency to patent a new technology and protect it in terms of intellectual property and the benefits arising from this patenting can delay access to a new technology for all people living in a less developed country, regardless of their age, thus ensuring different access and unequal distribution of the benefit of the emergence of these technologies. 57…”
Section: Introductionmentioning
confidence: 99%
“…The European Union, New Zealand, Norway, and Switzerland have to date consciously included crops and forages developed using New Breeding Technologies under the same legislation as all other GM crops. 4 , 7 , 32 , 194 , 285 This exposes contradictions. In Europe, importation of GM feed for animal is permitted but crops developed with GM technologies including those developed using New Breeding Technologies are regulated.…”
Section: Differentiating Between Different Types Of Genetic Manipulationmentioning
confidence: 99%
“…By overcoming the lack of efficiency of current methods, numerous applications would be accelerated, including (i) integration into genomes of cell lines used in industrial biotechnology for the production of pharmaceuticals and other proteins (6); (ii) introduction of desirable traits, such as disease resistance or enhanced nutritional content, into plant genomes (7,8); (iii) insertion of disease-related genes into genomes of animal models to study the mechanisms of various disorders and test therapeutic interventions (9); (iv) integration of genetic modules into synthetic genomes, allowing the creation of biological memory devices or genetic logic gates (10,11); (v) attachment of epitope tags or fusion proteins to study gene regulation and localization in situ or in vivo (12); and (vi) delivering therapeutic genes into the genomes of patients' cells (13)(14)(15). Tailoring a therapy to correct an individual's unique mutation is challenging, hence a full replacement of the coding sequence of a recessive gene is often needed for a single, common therapy to be effective (16). As treatments for increasingly complex diseases are undertaken, multi-gene insertions will be necessary requiring larger cargos beyond the limits of current virus-based approaches (17).…”
Section: Introductionmentioning
confidence: 99%